Expert System for Diagnosing Palm Tree Diseases and Pests using Forward Chaining and Certainty Factor - Reza Fauzan; Arsenio Virgian Prananda (Universitas Muhammadiyah Malang, 2018)
A general introduction to pests and diseases of palm oil crops in relation with the business of palm oil cultivation is necessary to increase the productivity of palm oil plantations. Unfortunately, the number of experts and researchers having expertise in palm oil plants are still very small. To overcome this, an expert system is needed to diagnose diseases and pests in palm oil crops. Therefore, this study proposes an expert system for diagnosing palm tree diseases and pests. The diagnosis begins by entering the initial symptoms, then the system will display other related symptoms. Finally, the system will display the diagnosis of the symptoms entered. This expert system will ease farmers in identifying diseases and pests based on early symptoms; hence, necessary prevention and early treatment of the disease can be accurately conducted.